Resolving Inconsistencies in Trends in Old-Age Disability: Report from a Technical Working Group - Freedman, Vicki A.; Crimmins, Eileen; Schoeni, Robert F.; Spillman, Brenda C.; Aykan, Hakan; Kramarow, Ellen; Land, Kenneth; Lubitz, James; Manton, Kenneth; Martin, Linda G.; Shinberg, Diane; Waidmann, Timothy (Demography, 2004)
In September 2002, a technical working group met to resolve previously published inconsistencies across national surveys in trends in activity limitations among the older population. The 12-person panel prepared estimates from five national data sets and investigated methodological sources of the inconsistencies among the population aged 70 and older from the early 1980s to 2001. Although the evidence was mixed for the 1980s and it is difficult to pinpoint when in the 1990s the decline began, during the mid- and late 1990s, the panel found consistent declines on the order of 1%-2.5% per year for two commonly used measures in the disability literature: difficulty with daily activities and help with daily activities. Mixed evidence was found for a third measure: the use of help or equipment with daily activities. The panel also found agreement across surveys that the proportion of older persons who receive help with bathing has declined at the same time as the proportion who use only equipment (but not personal care) to bathe has increased. In comparing findings across surveys, the panel found that the period, definition of disability, treatment of the institutionalized population, and age standardizing of results were important to consider. The implications of the findings for policy, national survey efforts, and further research are discussed.